Structure‐Based Design of Novel Human Toll‐like Receptor 8 Agonists. Issue 4 (28th January 2014) - Kokatla, Hari Prasad; Sil, Diptesh; Tanji, Hiromi; Ohto, Umeharu; Malladi, Subbalakshmi S.; Fox, Lauren M.; Shimizu, Toshiyoki; David, Sunil A.
Abstract Toll‐like receptor (TLR)‐8 agonists activate adaptive immune responses by inducing robust production of T helper 1‐polarizing cytokines, suggesting that TLR8‐active compounds might be promising candidate vaccine adjuvants. Recently, a C2‐butyl furo[2, 3‐c]quinoline was reported with purely TLR8 agonistic activity. This compound was successfully co‐crystallized with the human TLR8 ectodomain, and the co‐crystal structure revealed ligand‐induced reorganization of the binding pocket of TLR8. The loss of a key hydrogen bond between the oxygen atom of the furanyl ring of the agonist and Thr 574 in TLR8 suggested that the furan ring is dispensable. Employing a disconnection strategy, 3‐ and 4‐substituted aminoquinolines were investigated. Focused structure‐based ligand design studies led to the identification of 3‐pentyl‐quinoline‐2‐amine as a novel, structurally simple, and highly potent human TLR8‐specific agonist (EC50=0.2 μM). Preliminary evaluation of this compound in ex vivo human blood assay systems revealed that it retains prominent cytokine‐inducing activity. Together, these results indicate the suitability of this compound as a novel vaccine adjuvant, warranting further investigation.